Agrarian reform in the Brazilian Amazon: its implications for land distribution and deforestation - Pacheco, P. (2009)
This paper examines the interactions between state-led land reform, agrarian structures, and deforestation in the Brazilian Amazon. Land reform tends to promote land redistribution through regularization of smallholder land invasions of large-scale landholdings, and by redistribution of public lands to smallholders in existing colonization frontiers. The implications of state-led land reform on deforestation are heterogeneous. I argue that impacts of agrarian reform are strongly related to the pre-existing social and economic configuration of the frontiers where it takes place. While it leads to lower rates of deforestation in landscapes dominated by smallholders with diversified land use, its impact on forest conversion is higher in landscapes where extensive land use, mainly prompted by large-scale cattle ranching, tends to dominate. I provide an assessment for the whole Brazilian Amazon, and examine two research sites in the state of Para´, namely Uruara´ and Redenca˜o. The study is based on informant interviews, secondary information, agricultural census data, and remote sensing data.